Evaluasi Current Ratio sebagai Indikator Likuiditas dalam Laporan Keuangan 2020-2024 pada Bank BCA Syariah - Wahono, Dava Wahyu (Maliki Interdisciplinary Journal, 2025)
This study aims to evaluate the liquidity position of Bank BCA Syariah by analyzing the Current Ratio over the period 2020–2024. A descriptive quantitative approach is applied, using secondary data obtained from the bank’s annual financial reports. The Current Ratio is measured by comparing current assets with current liabilities to determine the bank’s capacity to meet its short-term obligations. The findings indicate that BCA Syariah’s liquidity performance fluctuated sharply throughout the observed period. Liquidity strengthened in 2021 and reached its highest point in 2022, but gradually declined in 2023 and dropped significantly in 2024. These variations were influenced by changes in financing activities, cash management, and the stability of third-party funds. This is influenced by internal factors, such as financing growth, cash management, and third-party fund management, as well as external variables, such as macroeconomic conditions.